2018
DOI: 10.1177/0363546517751683
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Follow-up Study Comparing Operative Versus Nonoperative Treatment of Anterior Cruciate Ligament Ruptures in High-Level Athletes

Abstract: In this retrospective pair-matched follow-up study, we found that after 20-year follow-up, there was no difference in knee osteoarthritis between operative versus nonoperative treatment when treatment was allocated on the basis of a patient's response to 3 months of nonoperative treatment. Although knee stability was better in the operative group, it did not result in better subjective and objective functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 47 publications
4
89
1
2
Order By: Relevance
“…Five percent of all people had suffered a previous ACL injury, and 2% went on to suffer a subsequent contralateral ACL injury. Following ACLR, graft rupture occurred in 5% of people, which is consistent with previously reported graft rupture rates (Crawford et al, 2013;Lai et al, 2017;van Yperen, Reijman, van Es, Bierma-Zeinstra, & Meuffels, 2018;Wright et al, 2011).…”
Section: Subsequent Acl Injurysupporting
confidence: 90%
“…Five percent of all people had suffered a previous ACL injury, and 2% went on to suffer a subsequent contralateral ACL injury. Following ACLR, graft rupture occurred in 5% of people, which is consistent with previously reported graft rupture rates (Crawford et al, 2013;Lai et al, 2017;van Yperen, Reijman, van Es, Bierma-Zeinstra, & Meuffels, 2018;Wright et al, 2011).…”
Section: Subsequent Acl Injurysupporting
confidence: 90%
“…Thus, the latter type of data is underpowered to disentangle whether clinically assessed alterations of the knee joint during rehabilitation from ACL reconstruction are due to surgery and physical activity or the individual musculoskeletal biology of the patient. Last, but not least, the open reconstructive surgery, and the post-operative cast immobilization ( Smith and Davies, 2008 ), deployed does not correspond to the state-of-art to address the studied clinical problem, which in instances is treated nowadays in a conservative manner despite a similar long term outcome as a surgical approach ( Culvenor et al, 2013 ; van Yperen et al, 2018 ). Within these mentioned boundaries, our manuscript provides novel relevant insight on the molecular and cellular mechanism underling the course of recovery of knee extensor function after open knee surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Routine clinical measurements were performed ( Gerber et al, 1985 ; Domnick et al, 2016 ; van Yperen et al, 2018 ). Knee stability and ACL injury was estimated with Lachmann and drawer test, the Pivot shift test, and by a radiological evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Eleven of the included studies 21 27 28 37 39 40 45-48 53 reported radiographic OA prevalence in the contralateral knee, ranging from 2% to 38%. Of these, five studies reported results from uninjured contralateral knees, 27 28 45 48 53 four studies 21 39 40 42 reported additional injuries to the contralateral knee (ACL injury, chondral lesion, meniscal injury, medial collateral ligament and lateral collateral ligament injury), while three studies 37 46 47 did not provide any information regarding additional injuries to the contralateral knee.…”
Section: Prevalence Of Radiographic Oamentioning
confidence: 99%